PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI HOTEL NOVUS GIRI RESORT AND SPA - Mey Veronica Pohan (LPPM Universitas Asa Indonesia, 2015)
Human resources is a very important thing in an organization either a profit or non profit organization. However, leadership is needed to develop and motivate people in organization. This study was conducted to determine how much influence the organizational culture and leadership to employees performance at Hotel Novus Giri Resort and Spa. Study took a sample of 80 respondents by random sampling technique and the type of research that the data collection techniques. While analysis of the data using qualitative and quantitative way through hypothesis testing with statistical tests include product moment correlation test, T-test and the coefficient of determination. Both organizational culture and leadership have drive a positive influence on the employees performances at Novus Hotel Giri Resort and Spa peak and as suggestions for motivating performance even harder, Giri Hotel Novus Resort and Sp. It is therefore hotel management should pay keen attention to the style of leadership that suitable to motivate employees to increase their performances.